Analysis of the Effect of Fuel System, Fuel Types and Spark Plug Types on CO2 Gas Exhaust using Factorial Design - Komarudin, Udin; Nuraeni Suryaman, Nia; Martoni; Hirary, Marisa (International Journal of Psychosocial Rehabilitation, 2020)
The vehicle combustion system, the type of fuel used, and the type of spark plugs are some of the variables that affect motor vehicle exhaust gases. Some exhaust gases (pollutants) by motorized vehicles include carbon dioxide (CO2), carbon monoxide (CO), sulfur dioxide (SO2), nitrogen monoxide (NOx), hydrocarbon (HC), and lead, smoke, and ash. Exhaust gases can pollute the air and greatly affect human health. From a number of variables that influence motorized exhaust gas, the author determines the combustion system variable, namely the carburetors and EFI types; the fuel variable type is Premium (octane 88) and Pertamax (octane 92); as well as the spark plug type variable and Iridium spark plugs, as variables main effect to analyze CO2 exhaust gas. The motorized vehicle used as a trial is a 4-step duck motorcycle, 110 cc. The test equipment used to analyze exhaust gas is the Kane Gas Analyzer (Class 1). The research method used is factorial design and variable analysis using Yates' algorithm, the same as in the previous experiment [1]. Yates’s algorithm analysis results that the effect of CO2 exhaust is the greatest due to the fuel system of 1.117 (EFI), the second effect is the type of fuel of 0.450 (Pertamax), and the third effect is the type of spark plug of -0.050 (standard spark plug).